2017
DOI: 10.1371/journal.pone.0175547
|View full text |Cite
|
Sign up to set email alerts
|

Association between hemoglobin glycation index with insulin resistance and carotid atherosclerosis in non-diabetic individuals

Abstract: Hemoglobin glycation index (HGI), defined as the difference between the observed HbA1c value and the value of HbA1c predicted from plasma glucose levels, represents a measure of the degree of non-enzymatic glycation of hemoglobin and it has been found to be positively associated with micro- and macro-vascular complications in subjects with type 2 diabetes. To investigate the pathophysiological abnormalities responsible for the increased cardiovascular risk of patients with higher HGI, we evaluated the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 53 publications
(71 reference statements)
9
63
1
Order By: Relevance
“…An increased HGI level, calculated using fasting plasma glucose concentration to predict HbA1c value, has been recently shown to identify a subgroup of the ACCORD population with a greater risk of diabetic complications, hypoglycemia and total mortality [22]. Moreover we have recently found that higher HGI levels may identify subjects with an increased risk of vascular atherosclerosis also among individuals without diabetes [27]. In the present cross-sectional study, for the first time, we report an association between HGI and liver steatosis in subjects not affected by diabetes.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…An increased HGI level, calculated using fasting plasma glucose concentration to predict HbA1c value, has been recently shown to identify a subgroup of the ACCORD population with a greater risk of diabetic complications, hypoglycemia and total mortality [22]. Moreover we have recently found that higher HGI levels may identify subjects with an increased risk of vascular atherosclerosis also among individuals without diabetes [27]. In the present cross-sectional study, for the first time, we report an association between HGI and liver steatosis in subjects not affected by diabetes.…”
Section: Discussionmentioning
confidence: 84%
“…The design of the CATAMERI study has been previously reported [14,[25][26][27]. The study cohorts include 2055 participants used to estimate the linear relationship between fasting plasma glucose and HbA1c in the study population to calculate the predicted HbA1c value, and 1120 individuals in whom hepatic steatosis was assessed by ultrasonography.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations